Exposure to predator models during the fertile period leads to higher levels of extra‐pair paternity in blue tits. Issue 2 (19th October 2019) - Santema, Peter; Valcu, Mihai; Kempenaers, Bart
Abstract: The perceived risk of predation can affect breeding behaviour and reduce reproductive success in prey species. Individuals exposed to predators may also adopt different mating tactics with potential consequences for the distribution of paternity in socially monogamous species that engage in extra‐pair copulations. We experimentally increased perceived predation risk during the fertile period in blue tits Cyanistes caeruleus . Every morning between nest completion and the onset of egg laying, we presented a model of either a predator or a non‐predator (control) near active nestboxes. Broods from pairs exposed to predators had higher levels of extra‐pair paternity than control broods. This mainly resulted from a higher proportion of extra‐pair offspring in broods with at least one extra‐pair young. Females exposed to predators first emerged from the nestbox later in the morning, stayed away from the nestbox for longer and were less likely to be visited at the nest by their social mate, but we detected no behavioural differences once the model was removed. Our results suggest that the higher rates of extra‐pair paternity resulted from the disruption of morning routines, which may have inhibited within‐pair copulations or increased opportunities for females to engage in extra‐pair copulations. We conclude that the perceived risk of predation can have substantial effects on levels of extra‐pair paternity. Abstract : Perceived predation risk can have many behavioural consequences, but how it affects mating behaviour has rarely been tested. The authors exposed blue tits to predator models during the peak fertile period and found that levels of extra‐pair paternity were substantially increased, possibly because early morning behaviour was disrupted.